(untitled) (Research, Society and Development, 2021)
Through the environmental perspective of producing new construction materials with the inclusion of tailings or residues that improve their properties and, at the same time, promote a practice that mitigates environmental impacts, the objective of this work is to diagnose the effect of incorporating scheelite- tailings as recycled aggregate in soil-cement bricks, partially replacing the soil, seeking to make its use feasible in interlocking pavements, as well as studying the physical-chemical properties of the mixing water used in the making of soil-cement bricks, originating from drains air conditioning system at IFPB Campus Campina Grande. The bricks produced used CP II Z-32 class cement, landfill cut-off soil for disposal, scheelite-tailings, and kneading water from air conditioning drains at the IFPB Campus Campina Grande. Conformation was performed manually with the aid of a hydraulic press, with subsequent curing at room temperature and periodic wetting during the first 7 days of cement hydration (alkaline stabilizer), until the ages of laboratory tests of compressive strength reached (28 days) and direct flexion (180 days). It was noted that the results of compressive strength exceeded the minimum limits of ABNT NBR 10834:2013, as well as the results of the flexion test demonstrated that the mechanical strength of the bricks is superior when incorporating the mineral tailings, a phenomenon also noticed through of the compressive strength test. The quality of the water used to manufacture the bricks, in addition to ensuring better chemical potential in the hydration reaction based on the state of the art, promotes a reduction in the use of water from the public supply, which comes from a relatively low water source.